Simulation-based learning in teacher education: Using Maslow’s Hierarchy of needs to conceptualize instructors’ needs - Frei-Landau, Rivi; Levin, Orna (Frontiers in Psychology, 2023)
Introduction Simulation-based learning (SBL) has become an effective tool in the education field, and instructors play a significant role in leading it. Although much is known about participants’ needs, SBL instructors’ needs have yet to be addressed. The study’s goal was to explore SBL instructors’ needs while guiding an SBL workshop using the psychological framework of Maslow’s Hierarchy of Needs. Methods We employed a qualitative case-study design, consisting of 68 four-hour-long workshops, held at a teacher-education simulation center by the center’s professional instructors. Data collection comprised 211 statements derived from instructors’ open-ended reflections, the transcripts of two focus groups held with the instructors, and 98 interpersonal communication documents. Results Data were analyzed using both deductive and inductive thematic analysis, which rendered 11 themes spanning Maslow’s five levels, and revealing two possible simulation-based learning paths: a complete process, in which all needs are met and an incomplete process, in which needs remain unmet. Discussion Theoretical insights and practical implications are provided for attending to instructors’ needs (i.e., basic needs, security, belonging, self-esteem, self-actualization) to ensure optimal learning in teacher education when using SBL.